Display : recent installation photographs from London galleries and venues - Lafuente, Pablo (London : Rachmaninoff's, 2005)
Austen, David ; Wermers, Nicole ; Ethridge, Roe ; Brown, Dan ; Brecht, George ; Brown, Glenn ; Guston, Philip ; Lichtenstein, Roy ; Levine, Sherrie ; Morris, Sarah ; Gidley, Tom ; Rosefeldt, Julian ; Skaer, Lucy et al.
boek